TIYANG TANI LAN TIKUS : MEWARISKAN NILAI PEKERTI BAGI ANAK MELALUI DONGENG KLASIK JAWA - -, Supartinah (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2007)
Besides being one of the efforts to have texts transformed into Indonesian,this article also aims at studying and describing the pitutur, or values reflectinggood character, in the Javanese text Tiyang Tani lan Tikus.The text Tiyang Tani lan Tikus (TTT) is one of the texts contained in thecodex Serat Dongeng Warni-Warni and belongs to the category of literarymanuscripts. The codex is part of a collection stored at the library of Sana Budaya,Yogyakarta, given the code number PB C 154 71 Rol. 144 No. 13. The manuscriptis in prose using Javanese orthography. It tells a story but the time of its writing andthe name of the person who copied it in writing are not mentioned. However, inview of the condition of the paper used, it could be estimated that it was written inthSurakarta early in the 20 century.The essential values of good character contained in the story of TiyangTani lan Tikus are of (1) simplicity in life, (2) empathy, (3) softness of heart, (4)loyalty or faithfulness, (5) spirit of togetherness, (6) love toward others, and (7)frugality. All those values could be developed into material for the teaching ofvalues to children. This is an important matter because, in one's development,childhood is a sensitive period for the optimum development of somepsychological aspects if the environment could give adequate stimulation. Storiesor fables told to children could become a means of stimulating the development ofsome psychological aspects of children so that they could hopefully gain theuppermost boundary of their range of potential development.Keywords: Javanese classical fables, values of good character